2022
DOI: 10.3389/fimmu.2022.890781
|View full text |Cite
|
Sign up to set email alerts
|

The Pioneer Transcription Factor Foxa2 Modulates T Helper Differentiation to Reduce Mouse Allergic Airway Disease

Abstract: Foxa2, a member of the Forkhead box (Fox) family of transcription factors, plays an important role in the regulation of lung function and lung tissue homeostasis. FOXA2 expression is reduced in the lung and airways epithelium of asthmatic patients and in mice absence of Foxa2 from the lung epithelium contributes to airway inflammation and goblet cell hyperplasia. Here we demonstrate a novel role for Foxa2 in the regulation of T helper differentiation and investigate its impact on lung inflammation. Conditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Many reports support the notion that HNF4A is a master regulator of hepatocyte phenotype and can regulate gene expression by binding promoter regions and coordinating lipolysis, p53, and bile acid signaling pathways, thereby preventing diet-induced NAFLD development ( Xu et al, 2021 ; Yang et al, 2021b ). RXR, ERRA and FOXA2 were reported to develop functions in lipid metabolism, endocrine, and immune system, respectively ( Wahab et al, 2019 ; Helmstädter et al, 2022 ; Yánez et al, 2022 ). Taken together, these screened TFs might be involved in the regulation of organ development and lipid metabolism during embryonic periods.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports support the notion that HNF4A is a master regulator of hepatocyte phenotype and can regulate gene expression by binding promoter regions and coordinating lipolysis, p53, and bile acid signaling pathways, thereby preventing diet-induced NAFLD development ( Xu et al, 2021 ; Yang et al, 2021b ). RXR, ERRA and FOXA2 were reported to develop functions in lipid metabolism, endocrine, and immune system, respectively ( Wahab et al, 2019 ; Helmstädter et al, 2022 ; Yánez et al, 2022 ). Taken together, these screened TFs might be involved in the regulation of organ development and lipid metabolism during embryonic periods.…”
Section: Discussionmentioning
confidence: 99%
“…FOXA2 in thymic epithelial cells (TECs) can promote positive selection of conventional CD4 T cells and regulate the generation and activity of Treg cells [46]. Conditional deletion of FOXA2 in T cells aggravates Th2 in ammation, increases differentiation towards Th2, and inhibits CD4 T cell differentiation towards Th1 in vitro [47]. FOXH1 (also known as FAST, forkhead activin signal transducer) is a transcriptional activation factor that plays an important role as a signaling intermediate of TGF-β family members (such as Activin and Nodal).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has verified FOXA2 as a promising molecular target in pulmonary diseases through reducing inflammation, oxidative stress and apoptosis. For example, Yánez et al ( 37 ) revealed that FOXA2 deletion in T cells aggravated the T helper 2 inflammatory response in allergic airway inflammation. Increase in FOXA2 can also weaken cigarette smoke extract-induced cell inflammation to delay the progression of chronic obstructive pulmonary disease ( 22 ).…”
Section: Discussionmentioning
confidence: 99%